Administrative Defects in Land Registration and Cancellation in the Perspective of Legal Justice - Fatkhul Muin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This research issue relates to land ownership as a function of the state to provide legal certainty to the community. Land registration as a procedure for land ownership is inseparable from efforts to protect the rights of every citizen to obtain land through various processes, therefore land ownership procedures must be fulfilled by every citizen, so as not to give birth to administrative defects in land ownership. Cancellation of land certificates based on article 29 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 concerning Handling and Settlement of Land Cases, that one of which can cancel land certificates due to administrative defects in land registration. This research focuses on administrative defects and cancellation of land certificates, using a legal approach in this analysis.